"The focus of architecture in education must be in the community": Interview with Jorge Marsino - Jorquera, Daniela (Base Diseño e Innovación, 2016)
Peruvian, but living in Chile as director—together with his partner Maria Ines Buzzoni—of Marsino Arquitectos Asociados, Jorge Marsino has devoted a large part of his career to develop architecture projects for public use buildings in the area of education. Twenty years ago, he faced his first project in this area as part of the studio of the late Manuel Moreno. With the passing of time, understood that the task in addition to developing a product was to understand what happens in a community and to design for the users. "We realized that the focus of architecture in education must be in the community," he emphasizes.